FAKTOR RISIKO KEJADIAN GIZI BURUK (SKOR Z BB/U) PADA BALITA DI WILAYAH KERJA PUSKESMAS CANDI LAMA TAHUN 2018 - Selli Marsellina Boru Sembiring; Siti Fatimah Pradigdo; Suyatno Suyatno (Jurnal Kesehatan Masyarakat (Undip), 2018)
Undernutrition is a severe level of nutritional problems caused by low intake of energy and protein from daily food and occurs for a long time. The purpose of this study was to determine the risk factors for the incidence of malnutrition in Puskesmas Candi Lama for 2018. It was a obrsevational research with case control design. Case groups ware toddlers with z-score <-3 SD while the control group is toddlers with z-score -2 SD  ≤ z ≤  2 SD. There ware 20 samples for each group selected by purposive sampling technique. The results were toddlers with lower 70% of RDA for energy (OR : ,4,500 95% CI:1,166-17,373), lower 70% of RDA for protein (OR : 5,571, 95% CI:1,420-21,860), and lower score appreciate of attitude (OR : 6,000, 95% CI:1,082-33,274) was the risk factor of undernutrition. Sex, age, infectious diseases, parenting, maternal education, maternal knowledge,maternal practice, maternal employment status, and family economic status wasn’t the risk factor of undernutrition. It can be concluded that risk factors of undernutrition in the Puskesmas Candi Lama was the % RDA of energy and protein adequacy, and maternal attitude.Highly recommended forhealth workers to always provide and share the information to the community in order to improve mothers’ nutritional knowledge of their children.